Measurement challenges for hydrogen vehicles. (19th July 2019) - Murugan, Arul; de Huu, Marc; Bacquart, Thomas; van Wijk, Janneke; Arrhenius, Karine; te Ronde, Indra; Hemfrey, David
Abstract: Uptake of hydrogen vehicles is an ideal solution for countries that face challenging targets for carbon dioxide reduction. The advantage of hydrogen fuel cell electric vehicles is that they behave in a very similar way to petrol engines yet they do not emit any carbon containing products during operation. The hydrogen industry currently faces the dilemma that they must meet certain measurement requirements (set by European legislation) but cannot do so due to a lack of available methods and standards. This paper outlines the four biggest measurement challenges that are faced by the hydrogen industry including flow metering, quality assurance, quality control and sampling. Highlights: There are four main measurement challenges for the hydrogen vehicles industry. Flow metering accuracy affects our ability to charge the customer correctly. Lack of quality assurance or control could destroy fuel cell in a hydrogen vehicle. Bad sampling of hydrogen at the station could lead to false purity analysis results. National Metrology Institutes could lead the effort to provide solutions for the challenges.